2007
DOI: 10.1159/000110608
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Pituitary Tumors

Abstract: Background: Pituitary tumors are common and usually grow insidiously over many years. Rarely fatal, treatment still requires multiple cytoreductive surgeries and/or radiation therapy with its attendant side effects. As a disease process of regulatory pathways, pituitary tumors offer numerous potential therapeutic targets, and many, such as the membranal dopamine2 and somatostatin receptors, have been successfully exploited for many years. Nuclear receptors, such as the estrogen receptor, peroxisome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that the tumorigenic effects of estrogens are primarily mediated by ERα. Lifetime exposure and high estrogen levels and thus high ER transcriptional activity represent a risk factor for developing tumors in breast [21] , endometrial [22] , ovarian [23] pituitary [24] and thyroid tissues [25] . In contrast, ERβ has been shown to possess a tumor suppressive effect in tissues such as the prostate [26] and colon [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the tumorigenic effects of estrogens are primarily mediated by ERα. Lifetime exposure and high estrogen levels and thus high ER transcriptional activity represent a risk factor for developing tumors in breast [21] , endometrial [22] , ovarian [23] pituitary [24] and thyroid tissues [25] . In contrast, ERβ has been shown to possess a tumor suppressive effect in tissues such as the prostate [26] and colon [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, pharmacological or molecular inhibition of Akt similarly reduces GH3 viability and NF‐κB binding, suggesting that the constitutive activation of NF‐κB observed in pituitary tumor cells may be, at least in part, mediated by Akt 74 . Thus, doxasozin, an alpha‐adrenoreceptor blocker that appears to inhibit nuclear signaling mediated by NF‐κB, may represent new medical therapy for some problematic pituitary tumors 75,76 …”
Section: Pituitary Tumorigenesis and Therapeutic Molecular Advancesmentioning
confidence: 99%
“…74 Thus, doxasozin, an alphaadrenoreceptor blocker that appears to inhibit nuclear signaling mediated by NF-B, may represent new medical therapy for some problematic pituitary tumors. 75,76 Another target of the PI3K/Akt pathway is mTOR. Previous studies have shown that rapamycin derivative RAD001 (everolimus) induces antiproliferative effects in GH-secreting pituitary tumor cells in vitro, by regulating cell cycle arrest.…”
Section: Targeting Therapies In Pituitary Adenomasmentioning
confidence: 99%